KUALITAS PELAYANAN BELLBOY DI FRONT OFFICE DEPARTMENT PANGERAN BEACH HOTEL PADANG - Fanny khazanah; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to determine the quality of bellboy service at the Pangeran Beach Padang hotel. This study uses quantitative methods to address the issues raised. The samples in this study were 98 people using purposive sampling technique. While the data collection techniques in this study used a questionnaire / questionnaire, observation and documentation. The collection technique used in this questionnaire is a Likert scale, then the data will be processed using quantitative methods whose data are numerical oriented on results in the form of conclusions that are certain and clear. Based on the results of research that has been done, there are 5 dimensions that will be examined on the quality of bellboy service at the Pangeran Beach Padang Hote. including responsive empathy assurance reliability tangible                                                                                               Keywords: Bellboy, Service Quality,Hotel